2017
DOI: 10.5812/jjcdc.57870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment Response and Side Effects of Spinal-Z in Patients with Metastatic Gastroesophageal Adenocarcinoma: A Double-Blind Randomized Controlled Trial

Abstract: Background: Spinal-Z is a methanolic mixture of dried seed powder of Peganum harmala Linn. and leaf of Dracocephalum kotschyi Boiss. It is available as oral capsules and has been used to treat various cancers. The aim of this study was to evaluate the effects of Spinal-Z capsules (containing herbal extracts) on blood parameters and gastrointestinal symptoms of patients with metastatic gastric adenocarcinoma and to determine its potential side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…7 Moreover methoxylated flavonoids in this plant have various biological and pharmacological qualities including antibacterial, antifungal, anti-inflammatory, antispasmodic, analgesic, antihyperlipidemic, and immunomodulatory properties. [8][9][10] The anticancer property of D. kotschi has been attributed to methoxylated flavones such as apigenin, luteolin, isokaempferid, crisimaritin, penduletin, and xanthomicrol, and the antioxidant activity might be due to the phenolic compounds (like caffeic acid, chlorogenic acid, phenylpropanoids, and flavonoids) present in this plant. 11 Dracocephalum kotschyi has also been used in traditional medicine for stomach and liver disorders, headache, and congestion, as a painkiller, and for the treatment of kidney complications, toothache, and colds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover methoxylated flavonoids in this plant have various biological and pharmacological qualities including antibacterial, antifungal, anti-inflammatory, antispasmodic, analgesic, antihyperlipidemic, and immunomodulatory properties. [8][9][10] The anticancer property of D. kotschi has been attributed to methoxylated flavones such as apigenin, luteolin, isokaempferid, crisimaritin, penduletin, and xanthomicrol, and the antioxidant activity might be due to the phenolic compounds (like caffeic acid, chlorogenic acid, phenylpropanoids, and flavonoids) present in this plant. 11 Dracocephalum kotschyi has also been used in traditional medicine for stomach and liver disorders, headache, and congestion, as a painkiller, and for the treatment of kidney complications, toothache, and colds.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthomicrol, the most common phytochemical composition in D. kotschyi leaves, possesses an anticancer effect . Moreover methoxylated flavonoids in this plant have various biological and pharmacological qualities including antibacterial, antifungal, anti‐inflammatory, antispasmodic, analgesic, antihyperlipidemic, and immunomodulatory properties . The anticancer property of D. kotschi has been attributed to methoxylated flavones such as apigenin, luteolin, isokaempferid, crisimaritin, penduletin, and xanthomicrol, and the antioxidant activity might be due to the phenolic compounds (like caffeic acid, chlorogenic acid, phenylpropanoids, and flavonoids) present in this plant .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, essential oils and aerial plant parts were the main components of the D. kotschyi plant that were investigated. Studies of different parts of D. kotschyi plant show that aerial parts of D. kotschyi plants are sources of valuable flavonoids and essential oils [10, 20, 44, 45] while its seeds are rich in linolenic, oleic, and linoleic acids [46]. According to Mashayekhan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies have confirmed some medicinal properties of D. kotschyi including antinociceptive [23], antihyperlipidemic [20], immunomodulatory [21], and cytotoxic [24] effects. The essential oil from D. kotschyi has strong spasmolytic activities on isolated ileum [67, 68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation